A management method of chronic diseases in the elderly based on IoT security environment. (September 2022) - Qin, Yue; Li, Xiaoli; Wu, Jia; Yu, Keping
Highlights: Infectious diseases are growing rapidly in the elderly and in the community IoT devices provide effective access to body data Immunization algorithms effectively predict transmission trends Abstract: Due to the global influenza pandemic and the increasing health problems of the elderly, healthcare for the elderly has become an important application of Internet of Things(IoT) technology. However, under the condition of smart healthcare, the privacy of the elderly is not well protected. Therefore, to ensure the information security of the elderly, this paper proposes a management method for elderly chronic diseases based on the IoT security environment, establishes a security protection mechanism, and uses the IoT technology to monitor the vital signs of the elderly in real-time. At the same time, the Disease Immune Rehabilitation Algorithm (DIRA) is constructed based on the physiological data collected by the device to identify healthy people and reduce the number of infected people. Through experiments on several generations, the results show that this method can increase the proportion of the immune population to a certain extent and reduce the number of infected people. Graphical abstract: Image, graphical abstract